Self-Regulatory Capacities Are Depleted in a Domain-Specific Manner - Zhang, Rui; Stock, Ann-Kathrin; Rzepus, Anneka; Beste, Christian (Frontiers in Systems Neuroscience, 2017)
Performing an act of self-regulation such as making decisions has been suggested to deplete a common limited resource, which impairs all subsequent self-regulatory actions (ego depletion theory). It has however remained unclear whether self-referred decisions truly impair behavioral control even in seemingly unrelated cognitive domains, and which neurophysiological mechanisms are affected by these potential depletion effects. In the current study, we therefore used an inter-individual design to compare two kinds of depletion, namely a self-referred choice-based depletion and a categorization-based switching depletion, to a non-depleted control group. We used a backward inhibition paradigm to assess the effects of depletion on task switching and associated inhibition processes. It was combined with EEG and source localization techniques to assess both behavioral and neurophysiological depletion effects. The results challenge the ego depletion theory in its current form: Opposing the theory’s prediction of a general limited resource, which should have yielded comparable effects in both depletion groups, or maybe even a larger depletion in the self-referred choice group, there were stronger performance impairments following a task domain-specific depletion (i.e. the switching-based depletion) than following a depletion based on self-referred choices. This suggests at least partly separate and independent resources for various cognitive control processes rather than just one joint resource for all self-regulation activities. The implications are crucial to consider for people making frequent far-reaching decisions e.g. in law or economy.